World Is at Stake: Arendt, the Anthropocene, and “Mankind’s Earthly Immortality” - Čerkez, Toni (HannahArendt.net, 2022)
Contrary to the narratives portraying Hannah Arendt’s work as “unhelpful” with the “wicked problem” of the Anthropocene, this article has argued that her reflections on modernity and the entanglements of capital, science, and technology offer a wealth of critical insight into conditions of Anthropocene’s emergence and its political characteristics. Thinking with Arendt about her concept of “action into nature”, ideas about “process” and new geocentrism, I argued that Arendt empowers the modern humans to grapple politically with the Anthropocene, instead of succumbing to the narratives of optimism (the “good Anthropocene”) or pessimism (apocalypse). Before offering such a conclusion, this article engaged Dipesh Chakrabarty’s most recent writing from an Arendtian perspective. Arguing pace Chakrabarty’s hopes for resuscitating wonder and reverence as characteristics of a new science and “new universalism” or new “global politics”, this article posited that since these two concepts were undermined in modernity by technology, science, and capitalism, which have objectified and ‘completed’ nature (planet), they are unhelpful in the Anthropocene. Instances of nostalgia were also strongly rejected by Arendt who preferred focusing on what can be done in the moment of “non-time-space”, that is in the space of ‘non-time’ that opens itself when different temporal forces of past and future collide into one another. Instead of resigning themselves to the linear space-time of “earthly immortality”, or ever-growing progress of capitalism, technology, and science, political action can help moderns in de-anthropomorphizing politics and re-centering the world and the planet as the loci of the political.